An unusual archosauriform tooth increases known tetrapod diversity in the lower Chinle Formation (Late Triassic) of southeastern Utah - Lopez,Andres; St. Aude,Isabella; Alderete,David; Alvarez,David; Aultman,Hannah; Busch,Dominique; Bustamante,Rogelio; Cirks,Leah; Lopez,Martin; Moncada,Adriana; Ortega,Elizabeth; Verdugo,Carlos; et al. (PeerJ PrePrints, 2015)
An unusual tetrapod tooth was discovered in the Late Triassic Chinle Formation of southeastern Utah. The tooth was originally thought to belong to Revueltosaurus but further investigations have rejected that hypothesis. In this paper we compare MNA V10668 to other known fossil teeth found in the Chinle Formation and identify the least inclusive clade it may belongs to. Using data found in other publications and pictures of other teeth, we compare this specimen to other Triassic dental taxa. MNA V10668 shares some similarities with Crosbysaurus, Tecovasaurus, and several other named taxa but possesses unique characteristics not found in other diapsid teeth. We conclude that it is most likely an archosauromorph and probably an archosauriform. This increases the known diversity of tetrapods from the Chinle Formation and represents the first tooth morphotype completely unique to Utah in the Late Triassic Period.
Keywords: archosaur; archosauriform; Chinle Formation; Triassic; tetrapod; dental taxon; Utah; Crosbysaurus; Revueltosaurus